Hearing in older adults with exfoliation syndrome/exfoliation glaucoma or primary open‐angle glaucoma. (7th November 2015) - Tryggvason, Geir; Jonasson, Fridbert; Cotch, Mary Frances; Li, Chuan‐Ming; Hoffman, Howard J.; Themann, Christa L.; Eiriksdottir, Gudny; Sverrisdottir, Jóhanna Eyrún; Harris, Tamara B.; Launer, Lenore J.; Gudnason, Vilmundur; Petersen, Hannes
Abstract: Purpose: To determine whether adults, aged 66–96 years, with exfoliation syndrome (XFS)/exfoliation glaucoma (XFG), or primary open‐angle glaucoma (POAG) have poorer hearing than controls of similar age. Methods: Case (XFS/XFG and POAG) and control status was diagnosed in the Reykjavik Glaucoma Studies (RGS) using slit‐lamp examination, visual field testing and optic disc photographs; the RGS data were merged with the Age, Gene/Environment Susceptibility–Reykjavik Study that collected hearing data using air‐conduction, pure‐tone thresholds obtained at 0.5, 1, 2, 3, 4, 6 and 8 kHz categorized by better ear and worse ear, based on pure‐tone averages (PTAs) calculated separately for low and middle frequencies (PTA512 – mean of thresholds at 0.5, 1 and 2 kHz) and high frequencies (PTA3468 – mean of thresholds at 3, 4, 6 and 8 kHz). Multivariable linear regression was used to test for differences in PTAs between cases and controls. Results: The mean age for 158 XFS/XFG cases (30.4% male) was 77.4 years, 95 POAG cases (35.8% male) was 77.9 years, and 123 controls (46.3% male) was 76.8 years. Using multivariable linear regression analysis, there were no consistent, statistically significant differences in PTAs between the two case groups and controls in either the low‐ or high‐frequency range, even when stratified by age group. Conclusion: Among the older individuals examined in this study hearing loss is highly prevalent and strongly associated with male gender and increasing age. As we did not find consistent statistically significant difference in hearing between cases and controls the diagnosis of XFS/XFG or POAG does not as such routinely call for audiological evaluation.